Research on the Construction of the Quality and Ability Improvement System for Student Cadres in the "141" Higher Education Institutions - Yin, Ningjin (Journal of Theory and Practice of Contemporary Education, 2023)
Student cadres in universities are an important force in carrying out ideological and political education work, and play an important role in cultivating morality and cultivating talents. Strengthening the cultivation of student cadres and improving their quality and abilities is of great practical significance. Based on a comprehensive analysis of the problems faced by university student cadres, this article proposes the "1441" student cadre quality and ability improvement system, which aims to form a student cadre awareness, construct a path to improve the quality and ability of "four refined" student cadres, and create a culture of "unity, unity, and daring to be the first" student cadre team.